Prevalence of coronary heart disease and cardiovascular risk factors in a national cross-sectional cohort study of systemic sclerosis. Issue 12 (24th April 2012) - Ngian, Gene-Siew; Sahhar, Joanne; Proudman, Susanna M; Stevens, Wendy; Wicks, Ian P; Van Doornum, Sharon
Abstract : Objectives: To determine the prevalence of coronary heart disease (CHD) and cardiovascular risk factors in a well-characterised cohort of systemic sclerosis (SSc) patients, and to compare this with the general population. Methods: A cross-sectional study of the prevalence of CHD and cardiovascular risk factors in participants in the Australian Scleroderma Cohort Study was performed. Controls were drawn from the 2007–8 National Health Survey (NHS) and the Australian Diabetes, Obesity and Lifestyle Study (AusDiab). OR and 95% CI were calculated to determine the prevalence of CHD and cardiovascular risk factors in SSc patients compared with controls. Results: Data were available for 850 SSc patients (86% female), 15 787 NHS participants (53% female) and 8802 AusDiab participants (56% female). Adjusted for age and gender, the OR of CHD in SSc patients was 1.9 (95% CI 1.4 to 2.4) compared with controls from AusDiab and 2.0 (95% CI 1.5 to 2.5) compared with controls from the NHS. The OR of CHD increased to 3.2 (95% CI 2.3 to 4.5) for SSc patients compared with controls from AusDiab after further adjustment for cardiovascular risk factors. Hypercholesterolaemia, diabetes mellitus and obesity were significantly less prevalent in the SSc cohort than in AusDiab. Within the SSc cohort, the presence of pulmonary arterial hypertension was associated with CHD. Conclusions: This is the first report of an increased prevalence of CHD in SSc patients. Further studies are required to determine the relative contribution of scleroderma-specific factors such as microvascular disease to the development of CHD.